2013
DOI: 10.5005/jp-journals-10024-1377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Efficacy and Cleaning Ability of Hand and Rotary Devices for Gutta-Percha Removal in Root Canal Retreatment: An in vitro Study

Abstract: The fastest technique to remove gutta-percha and the shortest time to reach working length was observed with ProTaper retreatment instruments with xylene followed by ProTaper retreatment files without xylene and Hedstrom files without xylene. After instrumentation for removal of gutta-percha, apical third was found to have more debris compared to coronal and middle 1/3 of the root canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This was in accordance with Dadresanfar et al (35) and Aly et al (31). On the contrary, Reddy et al (36) and Roshdy et al (37) reported that the apical part revealed the maximum residual filling material. This might attributable to the use of xylene as a solvent and single rooted teeth in the first study, and the use of bioceramic sealer in the second study.…”
Section: Discussionsupporting
confidence: 88%
“…This was in accordance with Dadresanfar et al (35) and Aly et al (31). On the contrary, Reddy et al (36) and Roshdy et al (37) reported that the apical part revealed the maximum residual filling material. This might attributable to the use of xylene as a solvent and single rooted teeth in the first study, and the use of bioceramic sealer in the second study.…”
Section: Discussionsupporting
confidence: 88%
“…With the advent of rotary instruments, studies have been conducted on their performance during endodontic retreatments. Thus, some systems achieved expressive results in terms of cleaning efficacy and time period when compared with manual technique [5,11,12,24].…”
Section: Discussionmentioning
confidence: 99%
“…These files have a convex triangular cross-section [26] similar to that of conventional Protaper files S and F. Moreover, D1 file has active point, making easy its initial penetration in the filling material [16,17]. This design improves the instrument's performance in terms of removing the filling material [24].…”
Section: Introductionmentioning
confidence: 99%
“…The application of solvent during root canal retreatment is controversy. It is known that solvents have been used to facilitate the process, but these should be used with care given their cytotoxic potential and the possibility of forming a residual film of softened gutta-percha on the root canal walls [12,13]. Taking it into account, in the present study, the solvent was restricted to the coronal portion of the gutta-percha, just to facilitate the initial penetration on the gutta-percha and the volume was minimal.…”
Section: Discussionmentioning
confidence: 99%